Análise jurídica sobre os impactos do garimpo ilegal em Cachoeira do Piriá/PA: possibilidades para REURB - LIMA, Tamires da Silva (2022)
This work seeks to analyze the limitations of Urban Land Regularization in the Municipality of Cachoeira de Piriá/PA. The hypothesis raised is the demonstration of the difficulties that hinder the REURB process in the Municipality of Cachoeira de Piriá/PA with the practice of illegal urban mining. The research techniques used were legislative and bibliographic. The general objective is to understand how the issues of illegal mining impact the REURB process in the Municipality of Cachoeira do Piriá/PA. And the specific objectives are: 1) To analyze the legal requirements of the REURB for the municipality of Cachoeira do Piriá/PA and the impacts of illegal mining; 2) Describe the aspects and impacts of illegal mining with the implementation of REURB in the municipality of Cachoeira do Piriá/PA and ;3) Indicate the difficulties that hinder REURB for the municipality of Cachoeira do Piriá/PA. In view of the above, it is understood that mining is related to a series of crimes and illegalities that produce serious socio environmental damage and accentuate the historical social inequality in the region, and therefore, the mining activity keeps the population away from extractivism and conservation of the environment. , without public policies to encourage family farming or access to social rights. In this vicious circle, the population sees mining as a possible alternative for improving living conditions, increasing environmental pollution and giving space to other illegalities.